STRATEGI MENSINERGIKAN PROGRAM PENGEMBANGAN MASYARAKAT DENGAN PROGRAM PEMBANGUNAN DAERAH - -, Akmaruzzaman; -, Sumardjo; Hariyoga, Himawan (Program Studi Manajemen Pembangunan Daerah. Fakultas Ekonomi dan Manajemen. IPB University, 2013)
Natuna regency is a rich area of natural resource products, but still includes underdeveloped areas in Riau Islands Province. Local governments have to make fundamental changes in building the infrastructure aspects, economic, and human resources to eliminate underdevelopment and reduce dependency on central government. The aims of this research are: (1). to evaluate the effectiveness and stakeholders’ perception of the CD program, in terms of participation and partnership; and (2) to formulate a strategy for synergizing the CD Program of Star Energy with the local government’s development program. The analytical methods that are used in this research are descriptive analysis and SWOT analysis. This research was undertaken in Palmatak Sub District and Siantan Sub District of Natuna District of Kepulauan Riau Province, from June until October, 2008. The results indicated that the government stakeholders perceived that the participation of the CD program’s beneficiaries was adequate, and that the partnership between Star Energy and the local government was inadequate. The result of SWOT analysis suggested that Star Energy needs to focus its CD program on sustainable activities, such as economic development and education programs. The strategy for increasing synergy with the local development programs is to intensify communication between the company and the local government through the formation of community development partnership forum.Keywords: Community Development (CD), Effectiveness, Policy Strategy